PENGARUH FASILITAS PELAYANAN ONLINE DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN (STUDI KASUS FORUM JUAL BELI TIBAN KOTA BATAM) - Wulandari, Suci Rahayu; Simanjuntak, Jontro (LPPM Universitas Putera Batam, 2021)
The purpose of this study was to determine the effect of online service facilities and product quality on customer satisfaction. A Case Study of the Batam City Tiban Buying and Selling Forum using simple random sampling technique. Test the quality of research data using validity and reliability tests, classical assumption test, effect test using multiple linear regression analysis, analysis of the coefficient of determination (R2), hypothesis testing using research (t test) and (f test) using the SPSS 25 software program. determination (R2) shows that the variable of online service facilities and product quality is 60.4% of customer satisfaction. The results of multiple linear regression tests show that online service facilities (X1) have an effect of 34.1% on customer satisfaction (Y) and product quality (X2) have an effect of 36.0% on customer satisfaction (Y). From the results of testing and testing the output that online service facilities have a positive and significant effect on customer satisfaction and product quality has a positive and significant effect on customer satisfaction, while online service facilities and product quality together have a positive and significant effect on customer satisfaction.